Climate Change Resilience and Public Education in Response to Hydrologic Extremes in Singapore - Chang, Chew Hung; Irvine, Kim N. (British Journal of Environment and Climate Change, 2014)
Aims: In February and March 2014, more than 300,000 households were affected by water rationing in Kuala Lumpur, Malaysia and the surrounding State of Selangor. Further south, reservoir levels in Singapore were dropping, prompting the government to raise the water conservation rhetoric, but falling short of implementing water rationing schemes. The region experienced a dry spell that was unprecedented in the last 30 years. Preparedness for storms has been the talk of the town since the 2001, 2006 and 2007 extreme high precipitation events in the southern parts of the peninsula and in Singapore resulted in costly flood damage. While resilience has been a concept used frequently in climate change adaptation, it is derived from ecology, where it refers to the capacity of the system to respond to a disturbance and resist the impact or recover from the damage of the disturbance. This paper examines the case of Singapore as an urban area in responding to a similar extreme hydrologic phenomenon by examining the climate Original Research Article British Journal of Environment & Climate Change, 4(3): 328-354, 2014 329 change resilience of the small city-state, with a view to recommending some considerations in designing climate change adaptation strategies. Place of Study: Singapore and peninsular Malaysia. Methodology: The paper reviews the rainfall extremes statistics covering the last 30 years for Singapore and then takes a hydrologic event-based case study approach to more closely examine the impact of record storms and the drought of March 2014 to discuss aspects of resilience that can serve as lessons for tropical cities in future adaptation to a climate-changing world. Results: Extreme rainfall events have become more frequent in Singapore over the past 30 years, while February, 2014 was the driest February since 1869. February, 2014 also had the lowest recorded daily relative humidity at 74.5%. Tropical cyclones are not expected to hit Singapore because of its location near the equator, yet Typhoon Vamei made history by delivering 210 mm of rain on 27 December, 2001. Between 19 and 20 December, 2007 Singapore received 366 mm of rain and within the same week another storm deposited 140 mm of rain in a 24 hour period. While there were some environmental and health impacts related to the February 2014 drought, including low dissolved oxygen levels in water and a localized fish kill, as well as reports of greater human respiratory problems, Singapore was able to weather the drought by requesting voluntary conservation measures, prudent reservoir management, and increasing the output of NEWater and desalinized water. Recent extreme rainfall events have produced localized flooding, but Singapore has progressively pursued a program of improved drainage, stream naturalization, and implementation of Low Impact Development (LID) technology to reduce flood-prone areas from 3,200 ha in the 1970’s to 36 ha today. Conclusion: We do not suggest that all countries need to have NEWater or desalinated water to solve drought problems. We do suggest that in managing rainfall related hazards, droughts and extremes have been treated rather independently. Based on the case study of extremes presented for Singapore we propose the importance of establishing a three-step preparedness program for extremes that includes Preparation (vulnerability and risk identification, adaptive capacity building, and monitoring), Response (information dissemination and relief action), and Recovery.
Keywords: C:Malaysia; C:Singapore; _z:class:countries; _z:class:themes; oa:keyword:hydrologic extremes; oa:sdg:13 Climate action; oa:topic:T10930 Global Flood Risk Assessment and Management; oa:topic:T11483 Tropical Cyclone Intensity and Climate Change; oa:topic:T12724 Integrated Management of Water, Energy, and Food Resources; openalex:import; openalex:yes